Centralized emergency control for multi-terminal VSC-based shipboard power systems. (January 2019) - Panasetsky, Daniil; Sidorov, Denis; Li, Yong; Ouyang, Li; Xiong, Jiamin; He, Li
Highlights: Proposed a concept of centralized reconfiguration algorithm for hybrid AC/DC SPS. The algorithm complements local control, paying particular attention to reconfiguration. A special emphasis is placed on improving the SPS reliability by combining the AC nodes. The modified DC-ZEDS model is used for case studies. Abstract: Multi-terminal hybrid AC/DC power systems have found a wide application in different areas, such as wind and solar energy, microgrids, shipboard power systems (SPS), etc. To ensure reliability and survivability of the SPS, the emergency control is necessary to be implemented, which is widely utilized in conventional AC networks and hybrid AC/DC systems. This paper proposes a concept of reconfiguration theory based on a centralized emergency control algorithm of the SPS with a complex structure, which has high requirements for reliability and survivability. The proposed method complements the well-proven local control approaches, paying particular attention to the SPS reconfiguration. A special emphasis is placed on improving the SPS reliability by combining the AC nodes, as well as on increasing the reconfiguration procedure efficiency, the latter being achieved by not taking into account the special constraint on the DC circuit breakers states. The algorithm carries out a preventive calculation of control actions using the genetic algorithm optimization procedure. The case studies were performed by using the modified DC zonal electrical distribution system (DC-ZEDS) model, and the results verify the feasibility and effectiveness of the proposed method and model.